Sulfide solid electrolyte membrane and preparation method and application thereof

Through the synergistic effect of polyurethane-modified PTFE and LiDFOB coated sulfide electrolyte and silane crosslinking, a high-performance sulfide solid electrolyte membrane was prepared, solving the problems of unstable interface, poor film formation performance and low ionic conductivity of the sulfide electrolyte, and achieving both mechanical strength and ionic conductivity.

CN120149520AActive Publication Date: 2025-06-13SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510622493.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-06-13
Estimated Expiration
2045-05-15

AI Technical Summary

Technical Problem

In practical applications, sulfide electrolytes face problems such as instability in interface, poor film formation performance, and low ionic conductivity, making it difficult to take into account both mechanical strength and ionic conductivity, and cracks and fractures are prone to occur during thinner preparation.

Method used

A high-performance sulfide solid electrolyte membrane was prepared by the triple synergistic effect of crosslinking of polyurethane-modified PTFE, LiDFOB coated sulfide electrolyte and methacryloyloxyalkylsilane. The method includes in-situ coating the sulfide electrolyte in LiDFOB/ethylene glycol dimethyl ether solution and forming a three-dimensional network structure by hot rolling.

Benefits of technology

The ultra-thin material preparation of sulfide solid electrolyte membrane is achieved, with toughness and high ionic conductivity, significantly improving interface stability and film formation performance, and solving the problem of difficult to take into account both mechanical strength and ion conductivity in traditional technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120149520A_ABST
    Figure CN120149520A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfide solid electrolyte membrane as well as a preparation method and application thereof, and relates to the technical field of all-solid-state batteries. The technical breakthrough is realized through a high-performance sulfide solid-state electrolyte membrane which is synergistically modified by polyurethane modified PTFE (Polytetrafluoroethylene), lithium difluoro (oxalato) borate coated sulfide electrolyte and silane crosslinking. The method comprises the following steps: firstly, modifying PTFE by using an active group (-NHCOO-) in a polyurethane molecule, and enabling a polar group and sulfide particles to form stable bonding; secondly, performing in-situ coating on the sulfide electrolyte in an ethylene glycol dimethyl ether solvent by using LiDFOB to construct a stable interface layer to inhibit side reaction; and finally, introducing a silane cross-linking agent, and carrying out hot pressing to form a three-dimensional network structure. And the obtained electrolyte membrane is good in membrane-forming property and high in ionic conductivity. The preparation process adopts dry molding, is free of a high-toxicity solvent, is simple and controllable in flow, is suitable for large-scale production, provides a technical scheme for industrialization of the sulfide all-solid-state battery, and effectively improves the cycling stability and the rate capability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of all-solid-state batteries, and particularly relates to a sulfide solid electrolyte membrane, a preparation method and an application thereof, and particularly relates to a high-performance sulfide solid electrolyte membrane modified by polyurethane-modified PTFE, lithium difluorooxalate borate-coated sulfide electrolyte and silane crosslinking, and a preparation process and an application thereof. Background Art

[0002] At present, lithium-ion battery technology is facing the dual challenges of energy density and safety. All-solid-state batteries have become an important direction to break through the existing technical bottlenecks due to their inherent safety characteristics. Sulfide-based solid electrolytes are regarded as the most potential electrolyte systems for practical applications due to their ionic conductivity comparable to that of liquid electrolytes and excellent mechanical ductility. However, sulfide electrolytes still face three major technical bottlenecks in practical applications: First, sulfide materials are extremely sensitive to moisture in the air and transition metal elements in electrode materials, and are prone to side reactions, resulting in an increase in interfacial impedance; Second, the degree of fibrillation of traditional PTFE binders is insufficient during the dry film-forming process, resulting in poor mechanical strength of the electrolyte membrane and difficulty in reducing the thickness (usually >100 μm); and traditional PTFE binders are difficult to form a uniform fiber network structure under mechanical shearing, resulting in structural defects in the electrolyte membrane; In addition, the interfacial compatibility between sulfide particles and polymer binders is poor, and phase separation is prone to occur during the film-forming process; and it is difficult to balance mechanical strength and ionic conductivity during the preparation of thin films (<50 μm), and cracks and fractures are likely to occur.

[0003] Therefore, developing a comprehensive solution that can simultaneously solve problems such as unstable interfaces, poor film-forming performance, and low ionic conductivity of sulfide electrolytes has become the key breakthrough point for promoting the industrialization of sulfide all-solid-state batteries. Summary of the Invention

[0004] In view of this, the purpose of the present invention is to provide a sulfide solid electrolyte membrane, a preparation method and an application thereof.

[0005] The purpose of the present invention is achieved by the following technical solutions: <The First Aspect> The present invention provides a preparation method for a LiDFOB-coated modified sulfide electrolyte. The steps are as follows: in-situ coating treatment of the sulfide electrolyte in a LiDFOB / dimethoxyethane solution, and the coated modified sulfide electrolyte is obtained after vacuum drying.

[0006] As an embodiment, the mass ratio of the solute LiDFOB to the solvent dimethoxyethane in the LiDFOB / dimethoxyethane solution is 1:(10~25).

[0007] In some embodiments, the mass ratio of the solute LiDFOB to the solvent ethylene glycol dimethyl ether in the LiDFOB / ethylene glycol dimethyl ether solution is 1 : (11.5 - 19).

[0008] As an embodiment, the mass ratio of the LiDFOB to the sulfide electrolyte is 1 : (8 - 20).

[0009] In some embodiments, the mass ratio of the LiDFOB to the sulfide electrolyte is 1 : (9 - 19.02).

[0010] As an embodiment, after adding ethylene glycol dimethyl ether solvent to the system before the in-situ coating treatment, the in-situ coating treatment is carried out.

[0011] As an embodiment, the mass ratio of the added ethylene glycol dimethyl ether solvent to the sulfide electrolyte is 1 : (1.8 - 2).

[0012] As an embodiment, the sulfide electrolyte is selected as Li 6 PS 5 Cl type.

[0013] As an embodiment, the method of the in-situ coating treatment is stirring at a speed of 600 - 1000 rpm for 5 - 10 h.

[0014] In some embodiments, the method of the in-situ coating treatment is stirring at a speed of 800 rpm for 5 h.

[0015] As an embodiment, the parameters of the vacuum drying are: the vacuum degree is 0.03 - 0.08 MPa, and keep warm at 40 - 80 °C for 5 - 10 h.

[0016] In some embodiments, the parameters of the vacuum drying are: the vacuum degree is 0.08 MPa, and keep warm at 60 °C for 10 h.

[0017] <Second aspect> The present invention provides a method for preparing a sulfide solid electrolyte membrane, comprising the following steps: S1. Uniformly mix a modified binder, a sulfide electrolyte modified by LiDFOB coating, and a crosslinking agent to obtain a mixture; S2. Perform hot roll pressing on the mixture to obtain the sulfide solid electrolyte membrane.

[0018] As an embodiment, the preparation method of the modified binder is: chemically graft-modify polytetrafluoroethylene in a polyurethane / acetonitrile solution, and then wash with deionized water and vacuum dry to obtain the modified binder.

[0019] As an embodiment, the method for preparing the polyurethane / acetonitrile solution is as follows: Add polyurethane into acetonitrile and mix evenly to obtain the polyurethane / acetonitrile solution, where the mass ratio of polyurethane to acetonitrile is (4 - 9) : 1.

[0020] As an embodiment, the mass ratio of polytetrafluoroethylene to the polyurethane / acetonitrile solution is 3 : (2.5 - 10).

[0021] As an embodiment, during the preparation of the modified binder, stirring is carried out at a speed of 600 - 1000 rpm to promote the chemical grafting modification reaction, and the reaction time is 4 - 8 h.

[0022] In some embodiments, during the preparation of the modified binder, stirring is carried out at a speed of 800 rpm to promote the chemical grafting modification reaction, and the reaction time is 4 h.

[0023] As an embodiment, the parameters for vacuum drying are as follows: the vacuum degree is 0.03 - 0.08 MPa, and it is kept warm at 40 - 80 °C for 5 - 10 h.

[0024] In some embodiments, the parameters for vacuum drying are as follows: the vacuum degree is 0.08 MPa, and it is kept warm at 60 °C for 10 h.

[0025] As an embodiment, the mass ratio of the modified binder, the coated and modified sulfide electrolyte, and the crosslinking agent is 98:1:1.

[0026] As an embodiment, the crosslinking agent is selected from silane coupling agents.

[0027] As an embodiment, the crosslinking agent is selected from methacryloxyalkylsilanes.

[0028] In some embodiments, the crosslinking agent is selected from G - 570.

[0029] As an embodiment, the parameters for mixing during preparation are as follows: at a speed of 5000 - 8000 rpm and the mixing time is 10 - 20 min.

[0030] In some embodiments, the parameters for mixing during preparation are as follows: at a speed of 5000 rpm and the mixing time is 10 min.

[0031] As an embodiment, the parameters for hot roll pressing treatment are as follows: temperature 50 - 60 °C, pressure 5 - 20 MPa, and the film - forming thickness is 50 - 120 μm.

[0032] In some embodiments, the parameters for hot roll pressing treatment are as follows: temperature 50 °C, pressure 10 MPa, and the film - forming thickness is 100 μm.

[0033] <The third aspect> The present invention provides a method for preparing a composite cathode material, comprising the following steps: Under an argon atmosphere, a ternary cathode material, a sulfide electrolyte coated with LiDFOB, and a conductive agent are mixed to obtain the composite cathode material.

[0034] As an embodiment, the mass ratio of the ternary cathode material, the sulfide electrolyte coated with LiDFOB, and the conductive agent is 80:15:5.

[0035] As an embodiment, the ternary cathode material is selected from one or more of NCM811, NCM622, and NCM523.

[0036] In some embodiments, the ternary cathode material is NCM811.

[0037] As an embodiment, the conductive agent is VGCF.

[0038] <The fourth aspect> The present invention provides a method for preparing a composite anode material, comprising the following steps: Under an argon atmosphere, a silicon anode material, a sulfide electrolyte coated with LiDFOB, and a conductive agent are mixed to obtain the composite anode material.

[0039] As an embodiment, the mass ratio of the silicon anode material, the sulfide electrolyte coated with LiDFOB, and the conductive agent is 6:3:1.

[0040] As an embodiment, the silicon anode material is selected from silicon powder, D 50 = 3 - 8 μm.

[0041] In some embodiments, the silicon anode material is silicon powder with D 50 = 5 μm.

[0042] As an embodiment, the conductive agent is VGCF.

[0043] <The fifth aspect> The present invention provides an application of a sulfide solid electrolyte membrane in a sulfide all - solid - state lithium battery.

[0044] As an embodiment, the electrolyte sheet in the battery is formed by pressing the above - mentioned sulfide solid electrolyte membrane.

[0045] As an embodiment, the positive electrode sheet in the battery is formed by pressing the above - mentioned composite cathode material.

[0046] As an embodiment, the negative electrode sheet in the battery is formed by pressing the above - mentioned composite anode material.

[0047] Compared with the prior art, the present invention has the following beneficial effects: (1) Through the triple synergistic effects of polyurethane-modified PTFE, LiDFOB-coated sulfide electrolyte, and crosslinking with methacryloxyalkylsilane, the present invention comprehensively improves the performance of the sulfide solid electrolyte membrane: In terms of physical properties, ultrathin films are successfully prepared, which have both toughness and high ionic conductivity; In terms of interface stability, a stable interface protection layer is constructed by chemically coating and modifying the interface of the sulfide electrolyte; In terms of process, a fully dry preparation process is adopted, avoiding the use of solvents, and having the characteristics of simple process, low cost, and environmental friendliness.

[0048] (2) The present invention effectively solves the key technical problems such as uneven fibrillation, many interfacial side reactions, and poor film-forming performance in the dry film-forming of sulfide electrolytes. Moreover, the entire preparation process does not require the use of highly toxic solvents, is fully compatible with the requirements of large-scale production, and provides a practical technical path for the industrial application of sulfide all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] By reading the following detailed description of non-limiting embodiments with reference to the accompanying drawings, other features, objects, and advantages of the present invention will become more apparent: Figure 1 It is a flowchart of a method for preparing a sulfide solid electrolyte membrane provided by the present invention; Figure 2 It is an SEM image of the sulfide solid electrolyte membrane prepared in Example 5 of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0050] The present invention will be described in detail below with reference to the embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that those of ordinary skill in the art can make several adjustments and improvements without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0051] For ease of understanding, the abbreviations or nouns mentioned below are first explained: PTFE: Polytetrafluoroethylene; LiDFOB: Lithium difluorooxalate borate; Silane coupling agent G-570: γ-methacryloxypropyltrimethoxysilane; VGCF: Carbon nanofiber conductive agent, VGCF-H, purchased from Kejing Zhida Technology Co., Ltd.; This specific embodiment provides a method for preparing a sulfide solid electrolyte membrane, which is a preparation method based on the synergistic effect of polyurethane graft-modified PTFE, lithium difluorooxalate borate-coated sulfide electrolyte, and silane crosslinking, as Figure 1 shown below. The steps are as follows: S1. Dry mixing: Add the modified PTFE, the coated and modified sulfide electrolyte, and the silane coupling agent as a crosslinking agent into a mixer for uniform mixing. Among them, The preparation steps of the modified PTFE are as follows: Chemically graft-modify polytetrafluoroethylene (PTFE) in a polyurethane / acetonitrile solution, then wash with deionized water and dry under vacuum to obtain the modified PTFE; The preparation steps of the coated and modified sulfide electrolyte are as follows: In-situ coat the sulfide electrolyte with a lithium salt (LiDFOB) in a 1,2-dimethoxyethane solvent, and obtain the coated and modified sulfide electrolyte after vacuum drying.

[0052] S2. Hot roll dry film forming: Hot press the mixture using a roll press to form a three-dimensional network structure during the hot pressing process, and obtain a sulfide solid electrolyte membrane with a certain toughness and thickness.

[0053] This specific embodiment also provides a method for using the coated and modified sulfide electrolyte prepared in step S12 above to prepare a composite cathode material.

[0054] This specific embodiment also provides a method for using the coated and modified sulfide electrolyte prepared in step S12 above to prepare a composite anode material.

[0055] This specific embodiment also provides a all-solid-state battery, which is formed by pressing the sulfide solid electrolyte membrane, composite cathode material, composite anode material, positive current collector, and negative current collector prepared above.

[0056] The above methods will be specifically introduced below through examples.

[0057] Example 1 This example provides a method for preparing a LiDFOB-coated and modified sulfide electrolyte. The steps are as follows: In an argon glove box, add 5 g of LiDFOB to 95 g of 1,2-dimethoxyethane, and stir well to form a uniform solution to obtain a LiDFOB / 1,2-dimethoxyethane solution; Add 10 g of Li 6 PS 5The Cl type sulfide solid electrolyte was added to 10.52 g of LiDFOB / ethylene glycol dimethyl ether solution, and then 5 g of ethylene glycol dimethyl ether solvent was added, and the mixture was reacted at room temperature at a magnetic stirring rate of 800 rpm for 5 h, and then vacuum dried at 60 ° C for 10 h with a vacuum degree of 0.08 MPa to obtain a lithium salt LiDFOB-coated modified sulfide electrolyte.

[0058] Example 2 This embodiment provides a method for preparing a LiDFOB-coated modified sulfide electrolyte, the steps of which are: In an argon glove box, 8 g of LiDFOB was added to 92 g of ethylene glycol dimethyl ether and stirred thoroughly to form a uniform solution, namely, LiDFOB / ethylene glycol dimethyl ether solution; 9g of Li 6 PS 5 The Cl type sulfide solid electrolyte was added to 12.5 g of LiDFOB / ethylene glycol dimethyl ether solution, and then 5 g of ethylene glycol dimethyl ether solvent was added, and the mixture was reacted at room temperature at a magnetic stirring rate of 800 rpm for 5 h, and then vacuum dried at 60 ° C for 10 h with a vacuum degree of 0.08 MPa to obtain a lithium salt LiDFOB-coated modified sulfide electrolyte.

[0059] Comparative Example 1 This comparative example provides an uncoated modified sulfide electrolyte, namely Li 6 PS 5 Cl type sulfide solid electrolyte.

[0060] Comparative Example 2 This comparative example provides a method for preparing a LiTFSI-coated modified sulfide electrolyte, and the steps are basically the same as those in Example 1, except that: Replace LiDFOB with LiTFSI.

[0061] Comparative Example 3 This comparative example provides a method for preparing a sulfide electrolyte using butyl butyrate as a solvent, and the steps are basically the same as those of Example 1, except that: Ethylene glycol dimethyl ether was replaced by butyl butyrate, and other parameters remained unchanged.

[0062] Example 3 This embodiment provides a method for preparing a modified PTFE, the steps are as follows: Add 10 g of polyurethane into 90 g of acetonitrile solvent and stir thoroughly to form a uniform solution to obtain a polyurethane / acetonitrile solution; 3 g of PTFE was added to 10 g of polyurethane / acetonitrile solution, and the reaction was carried out at a magnetic stirring rate of 800 rpm at room temperature for 4 h. Then it was washed 3 times with deionized water and vacuum dried at 60 °C for 10 h under a vacuum of 0.08 MPa to obtain a graft-modified PTFE binder.

[0063] Example 4 This example provides a method for preparing modified PTFE, and the steps are as follows: 20 g of polyurethane was added to 80 g of acetonitrile solvent and stirred thoroughly to form a homogeneous solution, named polyurethane / acetonitrile solution; 6 g of PTFE was added to 5 g of polyurethane / acetonitrile solution, and then 5 g of acetonitrile solvent was added. The reaction was carried out at a magnetic stirring rate of 800 rpm at room temperature for 4 h. Then it was washed 3 times with deionized water and vacuum dried at 60 °C for 10 h under a vacuum of 0.08 MPa to obtain a graft-modified PTFE binder.

[0064] Comparative Example 4 This comparative example provides an unmodified PTFE, that is, commercially available PTFE.

[0065] Example 5 This example provides a method for preparing a sulfide solid electrolyte membrane, and the steps are as follows: S1. 9.8 g of coated and modified sulfide electrolyte (prepared in Example 1), 0.1 g of modified PTFE binder (prepared in Example 3), and 0.1 g of silane coupling agent G-570 were added to a mixer for mixing. The mixer speed was 5000 rpm and the mixing time was 10 min to obtain a mixture.

[0066] S2. The mixture obtained in step S1 was hot-pressed using a roll press in an argon glove box. The temperature of the roll press was 50 °C, the pressure was 10 MPa, the roll rotation speed was 0.1 - 3.0 m / min (1.0 m / min in this example), and it was roll-pressed 6 times. The thickness of the formed film was 100 μm to obtain an electrolyte membrane, and the SEM test was as Figure 2 shown.

[0067] Example 6 This example provides a method for preparing a sulfide solid electrolyte membrane, and the steps are as follows: S1. 4.9 g of coated and modified sulfide electrolyte (prepared in Example 2), 0.05 g of modified PTFE binder (prepared in Example 4), and 0.05 g of silane coupling agent G-570 were added to a mixer for mixing. The mixer speed was 5000 rpm and the mixing time was 10 min to obtain a mixture.

[0068] S2. Hot press the mixture obtained in step S1 in an argon glove box using a roll press. The temperature of the roll press is 50°C, the pressure is 10 MPa, the rotational speed of the roll is 0.1 - 3.0 m / min (1.0 m / min in this embodiment), roll press 6 times, and the thickness of the formed film is 100 μm to obtain an electrolyte membrane.

[0069] Comparative Example 5 This comparative example provides a method for preparing a sulfide solid electrolyte membrane. The steps are basically the same as those of Example 5, with the difference being that: The modified PTFE prepared in Example 3 used is replaced with the unmodified PTFE of Comparative Example 4, and other parameters remain unchanged.

[0070] Comparative Example 6 This comparative example provides a method for preparing a sulfide solid electrolyte membrane. The steps are basically the same as those of Example 5, with the difference being that: The coated and modified sulfide electrolyte prepared in Example 1 used is replaced with the uncoated and unmodified sulfide electrolyte of Comparative Example 1, and other parameters remain unchanged.

[0071] Comparative Example 7 This comparative example provides a method for preparing a sulfide solid electrolyte membrane. The steps are basically the same as those of Example 5, with the difference being that: Do not add silane coupling agent, and other parameters remain unchanged.

[0072] Comparative Example 8 This comparative example provides a method for preparing a sulfide solid electrolyte membrane. The steps are basically the same as those of Example 5, with the difference being that: The coated and modified sulfide electrolyte prepared in Example 1 used is replaced with the LiTFSI-coated and modified sulfide electrolyte of Comparative Example 2, and other parameters remain unchanged.

[0073] Comparative Example 9 This comparative example provides a method for preparing a sulfide solid electrolyte membrane. The steps are basically the same as those of Example 5, with the difference being that: The coated and modified sulfide electrolyte prepared in Example 1 used is replaced with the sulfide electrolyte prepared using butyl butyrate as the solvent in Comparative Example 3, and other parameters remain unchanged.

[0074] Example 7 This example provides a method for preparing a composite cathode material, and the steps are as follows: In an argon glove box, 80 mg of NCM811 powder, 15 mg of LiDFOB-coated modified sulfide electrolyte (prepared in Example 1), and 5 mg of conductive agent VGCF powder were placed in a mortar and ground for 30 min to obtain a composite cathode material.

[0075] Example 8 This example provides a method for preparing a composite cathode material, and the steps are as follows: In an argon glove box, 80 mg of NCM811 powder, 15 mg of LiDFOB-coated modified sulfide electrolyte (prepared in Example 2), and 5 mg of conductive agent VGCF powder were placed in a mortar and ground for 30 min to obtain a composite cathode material.

[0076] Comparative Example 10 This comparative example provides a method for preparing a composite cathode material, and the steps are basically the same as those in Example 7, except that: The LiDFOB-coated modified sulfide electrolyte of Example 1 used was replaced with the uncoated modified sulfide electrolyte of Comparative Example 1, and other parameters remained unchanged.

[0077] Comparative Example 11 This comparative example provides a method for preparing a composite cathode material, and the steps are basically the same as those in Example 7, except that: The LiDFOB-coated modified sulfide electrolyte of Example 1 used was replaced with the LiTFSI-coated modified sulfide electrolyte of Comparative Example 2, and other parameters remained unchanged.

[0078] Comparative Example 12 This comparative example provides a method for preparing a composite cathode material, and the steps are basically the same as those in Example 7, except that: The LiDFOB-coated modified sulfide electrolyte of Example 1 used was replaced with the LiDFOB-coated modified sulfide electrolyte prepared when butyl butyrate was used as the solvent in Comparative Example 3, and other parameters remained unchanged.

[0079] Example 9 This example provides a method for preparing a composite anode material, and the steps are as follows: In an argon glove box, 60 mg of silicon powder, 30 mg of LiDFOB-coated modified sulfide electrolyte (prepared in Example 1), and 10 mg of conductive agent VGCF powder were placed in a mortar and ground for 30 min to obtain a composite anode material.

[0080] Example 10 This example provides a method for preparing a composite anode material, and the steps are as follows: In an argon glove box, 60 mg of silicon powder, 30 mg of the LiDFOB-coated modified sulfide electrolyte (prepared in Example 2), and 10 mg of the conductive agent VGCF powder were placed in a mortar and ground for 30 min to obtain a composite negative electrode material.

[0081] Comparative Example 13 This comparative example provides a method for preparing a composite negative electrode material. The steps are basically the same as those in Example 9, except that: The LiDFOB-coated modified sulfide electrolyte of Example 1 used was replaced with the uncoated modified sulfide electrolyte of Comparative Example 1, and other parameters remained unchanged.

[0082] Comparative Example 14 This comparative example provides a method for preparing a composite negative electrode material. The steps are basically the same as those in Example 9, except that: The LiDFOB-coated modified sulfide electrolyte of Example 1 used was replaced with the LiTFSI-coated modified sulfide electrolyte of Comparative Example 2, and other parameters remained unchanged.

[0083] Comparative Example 15 This comparative example provides a method for preparing a composite negative electrode material. The steps are basically the same as those in Example 9, except that: The LiDFOB-coated modified sulfide electrolyte of Example 1 used was replaced with the LiDFOB-coated modified sulfide electrolyte prepared using butyl butyrate as a solvent in Comparative Example 3, and other parameters remained unchanged.

[0084] Example 11 This example provides a method for preparing a sulfide all-solid-state lithium-ion battery, and the steps are as follows: In an argon glove box, the sulfide solid electrolyte membrane prepared in Example 5 was cut and placed in a pressure battery mold with a diameter of 10 mm, and pressed on a tablet press with a pressure of 1 ton and a pressure holding time of 1 min to obtain an electrolyte sheet; 30 mg of the composite positive electrode material prepared in Example 7 was spread on the surface of the electrolyte sheet, and pressed into a sheet on a tablet press with a pressure of 1 ton and a pressure holding time of 1 min, and a positive electrode sheet was covered on one side surface of the electrolyte sheet; 10 mg of the composite negative electrode material prepared in Example 9 was spread on the other side surface of the electrolyte sheet, and pressed into a sheet on a tablet press with a pressure of 1 ton and a pressure holding time of 1 min, and a negative electrode sheet was covered on the other side surface of the electrolyte sheet; A 10-mm-diameter and 15-μm-thick aluminum foil was placed on the surface of the positive electrode plate as the positive current collector, and a 15-μm-thick copper foil was placed on the surface of the negative electrode plate as the negative current collector. After assembly, a pressure of 1 ton was applied and held for 1 min for pressing to obtain a sulfide all-solid-state lithium-ion battery.

[0085] Example 12 This example provides a method for preparing a sulfide all-solid-state lithium-ion battery, and the steps are as follows: In an argon glove box, the sulfide solid electrolyte membrane prepared in Example 6 was cut and placed in a pressure battery mold with a diameter of 10 mm. A pressure of 1 ton was applied on a tablet press and held for 1 min for pressing to obtain an electrolyte sheet; 30 mg of the composite positive electrode material prepared in Example 8 was spread evenly on the surface of the electrolyte sheet, and a pressure of 1 ton was applied on a tablet press and held for 1 min to form a sheet, and a positive electrode plate was covered on one side surface of the electrolyte sheet; 10 mg of the composite negative electrode material prepared in Example 10 was spread evenly on the other side surface of the electrolyte sheet, and a pressure of 1 ton was applied on a tablet press and held for 1 min to form a sheet, and a negative electrode plate was covered on the other side surface of the electrolyte sheet; A 10-mm-diameter and 15-μm-thick aluminum foil was placed on the surface of the positive electrode plate as the positive current collector, and a 15-μm-thick copper foil was placed on the surface of the negative electrode plate as the negative current collector. After assembly, a pressure of 1 ton was applied and held for 1 min for pressing to obtain a sulfide all-solid-state lithium-ion battery.

[0086] This specific embodiment also provides several comparative examples of the method for preparing a sulfide all-solid-state lithium-ion battery. The steps are basically the same as those in Example 11, except for the selection of each sulfide solid electrolyte membrane, composite positive electrode material, and composite negative electrode material. See Table 1 for details.

[0087] Table 1

[0088] Comparative Example 16 This comparative example provides a method for preparing a sulfide all-solid-state lithium-ion battery. The steps are basically the same as those in Example 11, and the differences are as follows: The sulfide solid electrolyte membrane of Example 5 used was replaced with the electrolyte membrane prepared with unmodified PTFE in Comparative Example 5, and other parameters remained unchanged.

[0089] Comparative Example 17 This comparative example provides a method for preparing a sulfide all-solid-state lithium-ion battery. The steps are basically the same as those in Example 11, and the differences are as follows: Replace the sulfide solid electrolyte membrane of Example 5 used with the electrolyte membrane prepared from the uncoated and unmodified sulfide electrolyte in Comparative Example 6, replace the composite positive electrode in Example 7 used with the composite positive electrode prepared from the uncoated and unmodified sulfide electrolyte in Comparative Example 10, replace the composite negative electrode in Example 9 used with the composite negative electrode prepared from the uncoated and unmodified sulfide electrolyte in Comparative Example 13, and keep other parameters unchanged.

[0090] Comparative Example 18 This comparative example provides a method for preparing a sulfide all-solid-state lithium-ion battery. The steps are basically the same as those in Example 11, except that: Replace the sulfide solid electrolyte membrane of Example 5 used with the electrolyte membrane prepared from the uncoated and unmodified sulfide electrolyte in Comparative Example 6, and keep other parameters unchanged.

[0091] Comparative Example 19 This comparative example provides a method for preparing a sulfide all-solid-state lithium-ion battery. The steps are basically the same as those in Example 11, except that: Replace the sulfide solid electrolyte membrane of Example 5 used with the electrolyte membrane prepared without silane coupling agent in Comparative Example 7, and keep other parameters unchanged.

[0092] Comparative Example 20 This comparative example provides a method for preparing a sulfide all-solid-state lithium-ion battery. The steps are basically the same as those in Example 11, except that: Replace the sulfide solid electrolyte membrane of Example 5 used with the electrolyte membrane prepared from the sulfide electrolyte coated and modified with lithium salt LiTFSI in Comparative Example 8, replace the composite positive electrode in Example 7 used with the composite positive electrode prepared from the sulfide electrolyte coated and modified with lithium salt LiTFSI in Comparative Example 11, replace the composite negative electrode in Example 9 used with the composite negative electrode prepared from the sulfide electrolyte coated and modified with lithium salt LiTFSI in Comparative Example 14, and keep other parameters unchanged.

[0093] Comparative Example 21 This comparative example provides a method for preparing a sulfide all-solid-state lithium-ion battery. The steps are basically the same as those in Example 11, except that: Replace the sulfide solid electrolyte membrane of Example 5 used with the electrolyte membrane prepared from the sulfide electrolyte coated and modified with lithium salt LiTFSI in Comparative Example 8, and keep other parameters unchanged.

[0094] Comparative Example 22 This comparative example provides a method for preparing a sulfide all-solid-state lithium-ion battery. The steps are basically the same as those in Example 11, except that: Replace the sulfide solid electrolyte membrane of Example 5 used with the electrolyte membrane prepared from the sulfide electrolyte modified with butyl butyrate solvent in Comparative Example 9. Replace the composite positive electrode in Example 7 used with the composite positive electrode prepared from the sulfide electrolyte modified with butyl butyrate solvent in Comparative Example 12. Replace the composite negative electrode in Example 9 used with the composite negative electrode prepared from the sulfide electrolyte modified with butyl butyrate solvent in Comparative Example 15. Keep other parameters unchanged.

[0095] Comparative Example 23 This comparative example provides a method for preparing a sulfide all-solid-state lithium-ion battery. The steps are basically the same as those in Example 11, except that: Replace the sulfide solid electrolyte membrane of Example 5 used with the electrolyte membrane prepared from the sulfide electrolyte modified with butyl butyrate solvent in Comparative Example 9. Keep other parameters unchanged.

[0096] Detection and analysis Cut the sulfide solid electrolyte membranes prepared in Example 5, Example 6, and Comparative Examples 5 to 9 into small round pieces with a diameter of 10 mm, load them into a pressure battery mold, press for 1 min under a pressure of 1 ton, and the thickness after pressing corresponds to the data in Table 2. Use an electrochemical workstation with the model CHI660E to conduct an AC impedance test at room temperature. The test results are shown in Table 2.

[0097] Table 2

[0098] For the all-solid-state batteries prepared in Example 11, Example 12, and Comparative Examples 16 to 23, use a Neware battery test system with the model CT-4000 to conduct charge and discharge tests on the all-solid-state batteries. Use a charge and discharge step with a rate of 0.2C - 0.5C, a voltage range of 4.3 - 2.5V, and a temperature of 28°C to test the discharge capacity of the sulfide all-solid-state battery. The test results are shown in Table 3.

[0099] Table 3

[0100] As can be seen from Table 2, the ionic conductivities of the sulfide solid electrolyte membranes prepared in Example 5 and Example 6 are significantly higher than those in Comparative Examples 5 to 9, and the film-forming performance is better than that in Comparative Examples 5 to 9.

[0101] As can be seen from Table 3, the discharge capacities of the batteries in Example 11 and Example 12 at 0.2C and 0.5C are significantly higher than those in Comparative Examples 16 to 23, and the first-cycle Coulomb efficiency and the discharge efficiency at 0.5C are higher than those in several comparative examples. Moreover, the cycle stability after 30 cycles is higher than that in each comparative example.

[0102] The sulfide solid-state battery system constructed by the multi-dimensional modification strategy of the present invention realizes the synergistic improvement of interface compatibility and electrochemical stability, which is specifically reflected in: First, the PTFE is chemically modified by the active group (-NHCOO-) in the polyurethane molecule, which not only significantly improves the fibrillation ability of the binder, and the formed fiber network structure can increase the effective contact area with the electrolyte particles, thereby improving the film-forming property of the sulfide electrolyte. At the same time, the polar groups in the polyurethane molecular chain can form stable chemical bonds with the sulfide electrolyte particles, greatly improving the interface compatibility and solving the key problem of easy peeling at the electrode / electrolyte interface in the sulfide all-solid-state battery.

[0103] Second, LiDFOB is used to perform in-situ coating treatment on the sulfide electrolyte in the ethylene glycol dimethyl ether solvent, and a stable interface layer rich in LiF is constructed on the particle surface, and the borate groups in the coating layer can effectively inhibit the side reaction between the electrolyte and the electrode material, reduce the interface impedance, and improve the interface electrochemical stability.

[0104] Furthermore, methacryloxyalkylsilane (such as G-570) is introduced as a cross-linking agent, and a three-dimensional network structure is formed during the hot pressing process, which significantly improves the film-forming performance of the electrolyte membrane. At the same time, on the premise of maintaining high ionic conductivity, the cycle stability and rate performance of the sulfide all-solid-state battery are effectively improved.

[0105] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various deformations or modifications within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a LiDFOB-coated modified sulfide electrolyte, characterized in that: The sulfide electrolyte is subjected to in-situ coating treatment in a LiDFOB / ethylene glycol dimethyl ether solution, and the coated modified sulfide electrolyte is obtained after vacuum drying.

2. The method for preparing a sulfide electrolyte according to claim 1, characterized in that: It also includes one or more of the following technical features: A1, the mass ratio of the solute LiDFOB to the solvent ethylene glycol dimethyl ether in the LiDFOB / ethylene glycol dimethyl ether solution is 1: (10-25); B1, the mass ratio of the LiDFOB and the sulfide electrolyte is 1: (8~20); C1. Before the in-situ coating treatment, ethylene glycol dimethyl ether solvent is supplemented in the system, and then the in-situ coating treatment is performed, and the mass ratio of the supplemented ethylene glycol dimethyl ether solvent to the sulfide electrolyte is 1: (1.8-2); D1. The sulfide electrolyte is of Li6PS5Cl type; E1. The in-situ coating treatment is carried out by stirring at a speed of 600-1000 rpm for 5-10 hours; F1. The parameters of the vacuum drying are: vacuum degree 0.03-0.08 MPa, and heat preservation at 40-80°C for 5-10 hours.

3. A method for preparing a sulfide solid electrolyte membrane, characterized in that: The following steps are involved: S1, uniformly mixing the modified binder, the LiDFOB-coated modified sulfide electrolyte, and the cross-linking agent to obtain a mixture; S2, subjecting the mixed material to a hot roller pressing process to obtain the sulfide solid electrolyte membrane; The LiDFOB-coated modified sulfide electrolyte is prepared according to the method of claim 1 or 2; The preparation method of the modified binder is as follows: chemically grafting polytetrafluoroethylene in a polyurethane / acetonitrile solution, then washing with deionized water and vacuum drying.

4. The method for preparing an electrolyte membrane according to claim 3, characterized in that: The preparation process of the modified binder also includes one or more of the following technical features: A2. The preparation method of the polyurethane / acetonitrile solution is as follows: adding polyurethane to acetonitrile and mixing them uniformly to obtain the polyurethane / acetonitrile solution, wherein the mass ratio of the polyurethane to acetonitrile is (4-9): 1; B2, the mass ratio of the polytetrafluoroethylene to the polyurethane / acetonitrile solution is 3: (2.5-10); C2, stirring at 600-1000 rpm to promote chemical grafting modification reaction, the reaction time is 4-8 hours; D2. The parameters of the vacuum drying are: vacuum degree 0.03-0.08 MPa, and heat preservation at 40-80°C for 5-10 hours.

5. The method for preparing an electrolyte membrane according to claim 3, characterized in that: A3, the mass ratio of the modified binder, the coated modified sulfide electrolyte, and the crosslinking agent is 98:1:1; B3, the cross-linking agent is selected from silane coupling agent; C3, the parameters of the mixture during preparation are a rotation speed of 5000-8000 rpm and a mixing time of 10-20 min; D3. The parameters of the hot roller pressing treatment are: temperature 50~60°C, pressure 5~20MPa, and film thickness 50~120μm.

6. A method for preparing a composite positive electrode material, characterized in that: In an argon environment, a ternary positive electrode material, a LiDFOB-coated sulfide electrolyte, and a conductive agent are mixed to obtain the composite positive electrode material. The LiDFOB-coated sulfide electrolyte is prepared according to the method according to claim 1 or 2.

7. The method for preparing a composite positive electrode material according to claim 6, characterized in that: It also includes one or more of the following technical features: A4, the mass ratio of the ternary cathode material, the LiDFOB-coated sulfide electrolyte, and the conductive agent is 80:15:5; B4. The ternary positive electrode material is selected from one or more of NCM811, NCM622, and NCM523; C4. The conductive agent is VGCF.

8. A method for preparing a composite negative electrode material, characterized in that: In an argon environment, a silicon negative electrode material, a LiDFOB-coated sulfide electrolyte, and a conductive agent are mixed to obtain the composite negative electrode material, wherein the LiDFOB-coated sulfide electrolyte is Prepared according to the method of claim 1 or 2.

9. The method for preparing a composite negative electrode material according to claim 8, characterized in that: It also includes one or more of the following technical features: A5, the mass ratio of the silicon negative electrode material, the LiDFOB-coated sulfide electrolyte, and the conductive agent is 6:3:1; B5. The silicon negative electrode material is D 50 =3~8μm silicon powder; C5. The conductive agent is VGCF.

10. A sulfide all-solid-state lithium battery, characterized in that: The electrolyte sheet in the battery is pressed from a sulfide solid electrolyte membrane, and the sulfide solid electrolyte membrane is prepared according to the method described in any one of claims 3 to 5; the positive electrode sheet in the battery is pressed from a composite positive electrode material, and the composite positive electrode material is prepared according to the method described in claim 6 or 7; the negative electrode sheet in the battery is pressed from a composite negative electrode material, and the composite negative electrode material is prepared according to the method described in claim 8 or 9.

Citation Information

Patent Citations

  • Sulfide solid electrolyte layer, preparation method thereof and lithium ion battery

    CN114400368A

  • Composite solid electrolyte, composite solid electrolyte film and preparation method and application of composite solid electrolyte film

    CN116864786A

  • Modified inorganic electrolyte, composite solid electrolyte and application thereof

    CN118380639A

  • Method for improving performance of sulfur-based composite solid electrolyte film by regulating skeleton structure

    CN119009094A